Managing an Enterprise and Ethical Dilemmas in Accountancy - Wiśniewska, Jolanta (Olsztyn Economic Journal, 2014)
The purpose of this article is to present the correlation between management of an economic entity and the development of ethical accounting dilemmas in the era of high-risk business. In the globalisation era and recurring economic crises, realisation of the objectives of a company takes place under high risk conditions. It is therefore necessary to use a proper management system. The necessary condition for making all decisions is to have relevant information. The value and relevance of these decisions depend on the quality of information which they have been based on. Lack of ethics in accounting has a direct impact on the company's management, which is based on information generated by the accounting system of the company. Ethical dilemmas arising in accounting are also ethical dilemmas arising in the process of business management.